IL-33–mediated Eosinophilia Protects against Acute Lung Injury - Krishack, Paulette A. (Am J Respir Cell Mol Biol, 2021)
Pneumonia-induced lung injury and acute respiratory distress syndrome can develop because of an inappropriate inflammatory response to acute infections, leading to a compromised alveolar barrier. Recent work suggests that hospitalized patients with allergies/asthma are less likely to die of pulmonary infections and that there is a correlation between survival from acute respiratory distress syndrome and higher eosinophil counts; thus, we hypothesized that eosinophils associated with a type 2 immune response may protect against pneumonia-induced acute lung injury. To test this hypothesis, mice were treated with the type 2–initiating cytokine IL-33 intratracheally 3 days before induction of pneumonia with airway administration of a lethal dose of Staphylococcus aureus. Interestingly, IL-33 pretreatment promoted survival by inhibiting acute lung injury: amount of BAL fluid proinflammatory cytokines and pulmonary edema were both reduced, with an associated increase in oxygen saturation. Pulmonary neutrophilia was also reduced, whereas eosinophilia was strongly increased. This eosinophilia was key to protection; eosinophil reduction eliminated both IL-33–mediated protection against mortality and inhibition of neutrophilia and pulmonary edema. Together, these data reveal a novel role for eosinophils in protection against lung injury and suggest that modulation of pulmonary type 2 immunity may represent a novel therapeutic strategy.